Aggregate effect on the mechanical and fracture behaviours of concrete. (1st April 2023) - Zhao, Haiyang; Zhang, Liangchi; Wu, Zhonghuai; Liu, Ang; Imran, Muhammad
Highlights: Revealed different stress distribution and crack growth in concretes. Clarified aggregate effect on concrete mechanical behaviours. Explored the fracture mechanism based on crack growth rate in concretes. Abstract: Mechanical properties of concretes highly depend on aggregate inclusions. In-depth understandings of concrete fracture mechanisms and how aggregates influence the behaviours of concretes are crucial to applications. This paper highlights a systematic investigation on the effects of aggregate size and volume fraction on concrete fracture and mechanical behaviours by means of discrete element modelling (DEM). The present revealed the relations between the observable cracking in experiment with the interior stress distributions and crack growth, explored the fracture mechanism in terms of crack growth rate, and clarified the effect of aggregate size and volume fraction on the mechanical and fracture behaviours of concretes. The results of this study will subsequently navigate the design of fracture-resistant concrete materials. Graphical abstract: Image, graphical abstract